Arrhythmogenic right ventricular cardiomyopathy – evolution of electrocardiographic markers during long-term follow-up prior to ascertainment of diagnosis. (3rd October 2022) - Svensson, A; Carlson, J; Jensen, H K; Dahlberg, P; Bundgaard, H; Christensen, A H; Boonstra, M J; Svendsen, J H; Cadrin Tourigny, J; Te Riele, A S J; Platonov, P G
Abstract: Background: Depolarization and repolarization abnormalities are part of the diagnostic Task Force Criteria of 2010 (TFC2010) for arrhythmogenic right ventricular cardiomyopathy (ARVC). These abnormalities are thought to be progressive but have also been described as dynamic and sometimes reversible. Evolution of ECG abnormalities prior to clinical ARVC diagnosis is poorly studied. Objective: To assess the evolution of ECG depolarization and repolarization characteristics in patients with ARVC prior to diagnosis and to identify markers of disease progression at a preclinical stage. Methods: 353 patients with definite ARVC from Sweden, Denmark, the Netherlands and Canada with at least one 12-lead digital ECG (65% males, 67% probands, 56% mutation carriers, median age at diagnosis 42 [IQR 29–53] years and median age at first ECG 44 [30–55] years) were included. Digital ECGs were extracted from regional ECG archives. ECGs with left bundle branch block, ventricular pacing or recorded either prior to 15 years of age or after heart transplantation were excluded. Remaining 6, 871 ECGs were digitally processed and automatically analysed using the Glasgow algorithm. Median values for overall QRS duration, terminal activation delay (TAD) in lead V1 as well as amplitudes of QRS-T-components in precordial leads per patient per year were used for analyses and graphically represented using Lowess smoothing with cubic splines (Figure 1). Blue lines indicate smoothed conditional mean with 95% confidence interval (shadow). Time "0" (red line) indicates the time when TFC2010 were fulfilled for definite diagnosis. A database of 18, 564 anonymized digital ECGs (58% males, median age at latest ECG 41 years [IQR 32–52]) who were in contact with health care during 2020–2021 was processed using the same exclusion criteria and signal-processing methodology as in the ARVC group and used as a reference (black line). Results: TAD in lead V1 and overall QRS duration demonstrated a significant increase years before ARVC diagnosis, and significant reductions were seen in QRS-T voltages measured as R wave amplitude, QRS amplitude (the absolute sum of R wave and S wave), and T wave amplitude (Table 1 and Figure 1). The changes were seen in all precordial leads, not only the right-sided, and visually diverging from the controls. Conclusion: Development of the ARVC ECG phenotype started several years before diagnosis and continued afterwards. QRS duration and TAD increased, QRS voltages decrease, and T wave amplitude decreased eventually leading to T wave inversion. These changes might be visually assessed but also measured with available ECG software. These findings may be clinically useful in the screening and follow-up of ARVC relatives. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Governmental funding of clinical research (ALF), Region Ostergotland, Sweden.The Swedish Heart-Lung Foundation.